2011
DOI: 10.1371/journal.pone.0014775
|View full text |Cite
|
Sign up to set email alerts
|

IL1B Induced Smad 7 Negatively Regulates Gastrin Expression

Abstract: Background Helicobacter pylori elicited IL1B is one of the various modulators responsible for perturbation of acid secretion in gut. We have earlier reported that IL1B activated NFkB downregulates gastrin, a major modulator of acid secretion. However, we hypothesized that regulation of gastrin by IL1B would depend on the cell's ability to integrate inputs from multiple signaling pathways to generate appropriate biological response.Principal FindingIn this study, we report that IL1B induces Smad 7 expression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Specifically, Datta et al . reported that GAST mRNA expression can be repressed by IL-1β via Smad7 or NFκB activation [36] , [37] . Therefore we tested whether IL-1β suppresses GAST gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Datta et al . reported that GAST mRNA expression can be repressed by IL-1β via Smad7 or NFκB activation [36] , [37] . Therefore we tested whether IL-1β suppresses GAST gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Hepcidin is an antimicrobial peptide involved in iron metabolism homeostasis and is a regulator of gastric acid secretion (47). Gastrin is a regulator of gastric acid secretion that is negatively regulated by IL-1-␤ through the activation of NFB (55). H,K-ATPase is the parietal cell enzyme that mediates acid secretion and is also transcriptionally repressed by NFB (56).…”
Section: Discussionmentioning
confidence: 99%
“…IL1β inhibits gene expression of orexigenic ghrelin [ 32 ] and suppresses the production of gastric acid and gastrin [ 32 ]. However, it was shown recently that IL1β supports ectopic fat accumulation in hepatocytes and adipose-tissue macrophages [ 33 ]. Interestingly, high-fat-fed (HFF) mice exhibited a preferential increase of IL-1β concentration in portal compared to systemic blood [ 34 ], thus, indicating that the liver may differ in its IL-1β regulation from other perihearl tissues.…”
Section: Discussionmentioning
confidence: 99%